Managing portfolio managers : the impacts of market concentration, cross-sectional return dispersion and restrictions on short sales - Raubenheimer, Heidi (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.